Ammonium ionic liquids with anions of natural origin1. Issue 80 (2nd September 2015) - Pernak, Juliusz; Łęgosz, Bartosz; Walkiewicz, Filip; Klejdysz, Tomasz; Borkowski, Andrzej; Chrzanowski, Łukasz
<x xml:space="preserve">Abstract</x> Ammonium ionic liquids with anions of natural origin are biodegradable agents with antifeedant and anti-microbial activity.